PERFORMANCE OF BROILER GIVEN RATIONS CONTAINING MAGGOT (Hermetia illucens) AS A SOURCE OF PROTEIN - P. E. N., Putri; Mahardika, I G.; Astawa, I P. A. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aims to determine the effect of adding maggot in the ration on the performance of broiler. This research was conducted in Nyitdah Village, Kediri District, Tabanan Regency, Bali, which lasted for 8 weeks from September to October 2022. The design used was a completely randomized design (CRD) consisting of four treatments and four replications. Each replicate contained four broiler. The treatments given were commercial rations without the addition of maggot (P2), rations with 5% addition of maggot (P1), rations with 10% addition of maggot (P2), and rations with 15% addition of maggot (P3). The variables observed were ration consumption, initial and final weight gain, body weight gain, and feed conversion ratio. The results showed that the addition of maggot at the 5%, 10%, and 15% levels increased ration consumption, weight gain, and final weight, but did not have a significant effect on FCR. Based on the results of this study it can be concluded that the use of 5% maggot in broiler rations can increase broiler productivity and get the lowest FCR value.